Trauma and Treatment in Gillian Flynn’s Sharp Objects through Judith Herman’s Theories - Mehrgan Rezaeian; Behzad Pourgharib; Abdolbaghi Rezaei Talarposhti (Critical Literary Studies)
As an important event in the life of a person, childhood trauma demonstrates its aftermath through post-traumatic stress disorder symptoms, besides shaping a person’s self-perception and identity. The three main characters in Sharp Objects by Gillian Flynn suffer from multiple categories of trauma, including generational emotional abuse by female abusers. Therefore, it enables the possibility of having a psychoanalytical study of the novel concentrated on childhood trauma in three generations, with the help of trauma studies as elaborated by Judith Herman. This study aims at applying her trauma theory to Flynn’s work in order to unfold the traumatic childhood of its protagonist, Camille Preaker, and two other characters. The study illustrates that Preaker's relationship with her family is affected by memories of emotional neglect and self-harm, and how her identity and relationships have been influenced by trauma. Examining the initial traumatic events can aid in comprehending the characters' conduct, as it is the trauma that influences their social interactions and reactions to circumstances. The research indicates that childhood trauma, particularly emotional abuse from female abusers across generations, has enduring effects on mental health, such as changes in personality and loss of identity.